Clinical Impact of Preoperative Neutrophil-Lymphocyte Ratio in Renal Cell Carcinoma in Sardjito Hospital - Bagus Gilang Samudra; Aria Danurdoro; Danarto Danarto (National Cancer Center - Dharmais Cancer Hospital, 2021)
Background: Renal cell carcinoma (RCC) is one of the most common malignancies in the kidney and causes a mortality rate of more than 100,000 each year globally. The neutrophil-lymphocyte ratio (NLR) is one of the markers in the inflammatory response that also correlate with the alteration of any cancer cells. We investigated the correlation between the NLR on tumor stage, Fuhrman nuclear grade, length of stay (LOS), mortality, and recurrence rate in renal cell carcinoma.Methods: We investigated 52 patients with renal cell carcinoma retrospectively from the databases of the patients who underwent radical and partial nephrectomy in Sardjito Hospital Yogyakarta between 2012 and 2017. Patients were classified as lower stage (T1-T2) and higher stage (T3-T4). We also classified it as a group of Fuhrman nuclear grade (G1, G2, G3, and G4). Two sample t-test or one-way ANOVA was used for the continuous variables and a chi-square test or Fisher’s exact test for the categorical variables. Pearson test was used to do the correlation test.Results: Among a total of 52 patients analyzed in our study, there were 36 males (69%) and 16 females (31%). A normal distribution of datasets was verified. The mean of preoperative NLR in these 52 patients was 6.35 (+4.01), with a range of 1.48 - 21.0. The value of NLR was positively correlated with tumor pathologic stage (p = 0.020), length of stay of the patients (p = 0.00), and the mortality rate (p = 0.012). Neutrophil lymphocyte ratio was not significantly correlated with Fuhrman tumor grade (p = 0.357) and tumor recurrence (p = 0.670).Conclusions: We compared the relationship of preoperative NLR with renal cell carcinoma tumor stage (T), Fuhrman grade, length of stay, mortality, and tumor recurrence. NLR was found to have a statistically significant higher T stage, mortality, and length of stay of the patients. Further studies with more patients are needed to confirm our study.